How I do it: lateral canthal web revision—single Z-plasty technique - James Fowler; Corey C. Moore (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Lateral canthal webbing is a known complication of blepharoplasty, which occurs when the lateral aspect of the upper blepharoplasty incision is taken below the equator of the lateral canthus. Removing excessive eyelid skin laterally can also result in a lateral canthal web. Currently, there is no standard approach for addressing this complication. Methods Retrospective review of single surgeon practice between 2011 and 2019. All patients underwent revision surgery using the proposed single Z-plasty technique. Results Twenty-three patients referred for lateral canthal web were included in the study. All patients had previous upper lid blepharoplasty, with the initial procedure occurring 8–63 months prior to the referral for revision. The majority of the blepharoplasties occurred in Ontario (n = 19), but some patients also underwent surgery in Alberta (n = 1), British Columbia (n = 1), and United States (n = 1). The initial surgeries were performed by a variety of specialities including plastic surgery (n = 16), otolaryngology (n = 4), ophthalmology (n = 2), and family medicine (n = 1). Following revision surgery using the single Z-plasty technique, all patients reported a subjective increase in functional and aesthetic satisfaction. No further revision surgery was required for any of these patients. Conclusion The single Z-plasty technique is simple, robust, and could be easily incorporated into any cosmetic practice to address this complication of blepharoplasty. Graphical Abstract